2003
DOI: 10.1073/pnas.2232815100
|View full text |Cite
|
Sign up to set email alerts
|

The low gonadotropin-independent constitutive production of testicular testosterone is sufficient to maintain spermatogenesis

Abstract: Spermatogenesis is thought to critically depend on the high intratesticular testosterone (T) levels induced by gonadotropic hormones. Strategies for hormonal male contraception are based on disruption of this regulatory mechanism through blockage of gonadotropin secretion. Although exogenous T or T plus progestin treatments efficiently block gonadotropin secretion and suppress testicular T production, only Ϸ60% of treated Caucasian men reach contraceptive azoospermia. We now report that in luteinizing hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 37 publications
6
80
0
5
Order By: Relevance
“…However, these constant low levels of testosterone did not impair spermatogenesis, consistent with similar findings in the LH receptor KO mice, where intratesticular testosterone is suppressed to 2% of wild type, yet LH-independent autonomous steroidogenesis is sufficient to maintain spermatogenesis (30).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, these constant low levels of testosterone did not impair spermatogenesis, consistent with similar findings in the LH receptor KO mice, where intratesticular testosterone is suppressed to 2% of wild type, yet LH-independent autonomous steroidogenesis is sufficient to maintain spermatogenesis (30).…”
Section: Discussionsupporting
confidence: 85%
“…It is known that testosterone is essential for normal spermatogenesis, but questions remain about the minimum levels required, which varies by species. In mice, only minimal amounts of testosterone are required to maintain spermatogenesis (30), whereas suppression of steroidogenesis in rat, monkey, and human is the basis for the first generation of hormonal contraceptives (31). In addition, studies performed with female PACAP Ϫ/Ϫ mice showed that fertility is affected in these animals (32), raising the possibility that PACAP is likely to be an important regulator of reproductive functions in both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, poorly developed secondary sex characteristics and infertility are observed in both sexes. Further detail about the phenotype of this model are in our previous reports (Zhang et al, 2001a;Zhang et al, 2003;Zhang et al, 2004;Pakarainen et al, 2005c;Pakarainen et al, 2005b;Pakarainen et al, 2005a).…”
Section: Lh/hcg-r Knockout (Lurko) Micementioning
confidence: 99%
“…At the age of 4 months, the VIP KO mice display very low testosterone and lower FSH levels when compared with WT. These two factors are essential for the maintenance of spermatogenesis (Simoni et al 1999, Zhang et al 2003.…”
Section: Vip Action On Testicular Steroidogenesismentioning
confidence: 99%